Unsweetpotato – Breeding staple-type sweetpotato for West Africa and beyond - International Potato Center (2014)
An applied, collaborative sweetpotato breeding program and support platform for West Africa was established in Ghana at the CSIR-Crops Research Institute in 2010. Consumer demand for staple-type (low sugar) or Unsweetpotato was confirmed and laboratory methods to assist with election developed and used in a new Quality Laboratory. Seed populations were made available for distribution to regional partners.